Patterns of orthopedic injuries associated with increasing e-scooter-related trauma: A retrospective observational study with a 4-year evaluation from a tertiary center in Istanbul, Turkey - Senel, Ahmet; Sert, Selman; Aktas, Mehmet Akif; Tekin, Saltuk Bugra; Carkci, Engin; Erdogan, Sinan (Medicine (Baltimore), 2024)
The increasing use of electric scooters (e-scooters) has been accompanied by an increase in the number of traumas. Noncompliance with regulations and the effectiveness of legal measures remain subjects of ongoing debate. This study aimed to investigate the demographic characteristics of patients with e-scooter-related orthopedic injuries, temporal distribution of trauma, and patterns of these injuries. We retrospectively evaluated 534 patients with e-scooter-related injuries who were referred to the Department of Orthopedics and Traumatology between January 2020 and October 2023. Variables such as patient sex, age, time of trauma, type of hospital transfer, mechanism of trauma, injury location and type, accompanying head trauma in extremity injuries, and treatment approach were recorded. Temporal analysis was performed by hour, day, month, season, and weekday versus weekend. The majority of patients were male (80.0%), with injuries most common in the 25 to 39 age group (33.7%). Trauma was frequent in the summer (45.7%), especially in July (16.5%), with most hospital visits occurring on Fridays (18.2%) and weekends (32.2%). Blunt soft tissue injuries (47.3%) and fractures (42.4%) were prevalent, particularly in the elbow (18.4%), wrist (16.9%), and knees (14.3%). A total of 247 fractures were identified, with the radial head (17.0%) and distal radius (10.9%) being the most common fractures. Fracture rates have increased in 2022 and 2023 compared to those in previous years. While 86.0% of patients received nonsurgical treatment, 14.0% underwent surgery, with a rise in surgical cases in 2022 and 2023. Elbow (19.0%), knee (16.7%), and wrist (16.7%) were the most frequent surgical sites. The increasing use of e-scooters among young people has increased trauma cases, with a growing proportion of fractures over time. The higher incidence of injuries, particularly in the elbow and knee joints, underscores the importance of protective equipment. Therefore, additional legal regulations can help to prevent such injuries.